2010
DOI: 10.1177/0256090920100203
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adoption of Yoga Way of Life on the Reduction of Job Burnout of Managers

Abstract: Burnout is a prolonged response to chronic emotional and interpersonal stressors on the job, and is defined by the three dimensions of exhaustion, cynicism, and inefficacy. Job burn-out is a debilitating psychological condition, which has serious repercussions for an individual's personal health as also on the organizational effectiveness. The past 25 years of research has established the complexity of the construct, and has placed the individual stress experience within a larger organizational context of peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…In recent times, the professed healing properties of yoga and meditation practices have been empirically tested by researchers by investigating the effects of these practices on psychological and physiological indicators of stress. For example, a field experiment conducted in an Indian corporation showed that adoption of the yoga way of life could lead to significant reduction in burnout as compared to exercising (Adhia et al, 2010). Similarly, use of yoga and meditation techniques led to a reduction in pulse and systolic blood pressure (Bruning and Frew, 1987).…”
Section: Effects Of Sky and The Apex Programmementioning
confidence: 99%
“…In recent times, the professed healing properties of yoga and meditation practices have been empirically tested by researchers by investigating the effects of these practices on psychological and physiological indicators of stress. For example, a field experiment conducted in an Indian corporation showed that adoption of the yoga way of life could lead to significant reduction in burnout as compared to exercising (Adhia et al, 2010). Similarly, use of yoga and meditation techniques led to a reduction in pulse and systolic blood pressure (Bruning and Frew, 1987).…”
Section: Effects Of Sky and The Apex Programmementioning
confidence: 99%
“…The effect sizes, Cohen's d were calculated using an online effect size calculator. 3 The effect size is the highest for the self-report variable self-compassion. Moreover, the effect sizes for the physiological variables fall within the medium range.…”
Section: Resultsmentioning
confidence: 96%
“…In the Indian context, there have been studies exploring the impact of various yoga-based interventions in reducing stress (e.g., Adhia et al, 2010; Jawahar, 2012; Mulla & Vedamuthachar, 2014; Soni et al, 2015). However, there has so far not been any study which has investigated the effect of MBSR on psychological and physiological outcomes for individuals in Indian organizations.…”
Section: Rationale For This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Yoga way of life can reduce the job burnout of managers and thus helping employees to be healthy at the same time. [ 45 ]…”
Section: Model Of Yoga Intervention In Reducing Counterproductive Wormentioning
confidence: 99%